MaxEnt Modeling and Effects of Climate Change on Shifts in Habitat Suitability for Sorbus alnifolia in China - Yan Luo; Jingshi Yang; Luping Liu; Keliang Zhang (Plants)
Anthropogenic climate change stands out as one of the primary forces expected to reshape Earth’s ecosystems and global biodiversity in the coming decades. Sorbus alnifolia, which occurs in deciduous forests, is valued for its ornamental appeal and practical uses but is reported to be declining in the wild. Nevertheless, the distribution of this species’ suitable range, along with the key ecological and environmental drivers that shape its habitat suitability, remains largely unknown. By analyzing 198 occurrence records and 54 environmental factors, we employed MaxEnt to project S. alnifolia’s current and future habitat suitability. Our results showed that annual precipitation (37.4%), normalized difference vegetation index (30.0%), August water vapor pressure (20.8%), and temperature annual range (3.4%) were the most significant variables explaining S. alnifolia’s environmental requirements. The suitable habitats were primarily scattered across eastern and central China. Under projected future climatic conditions, the total expanse of potential habitat is expected to increase. However, most of this expansion involves low-suitability habitats, whereas moderately and highly suitable habitats are likely to shrink, especially in southern and lower-altitude regions of China. Based on these findings, we propose several conservation strategies to support the long-term sustainability of S. alnifolia.